China - Can Classroom Observations Measure Improvements in Teaching? - World Bank (World Bank, Washington, DC, 2020)
The results in education for all children (REACH) trust fund at the World Bank has funded a pilot of the classroom assessment scoring system (CLASS) in Guangdong, China to test its usefulness as a tool to assess teaching practices. The pilot was also designed to establish a proof of concept for using classroom observations to measure the impact of teacher training and incentivize training providers within an RBF mechanism. In the pilot, the CLASS tool was used to conduct classroom observations of 36 teachers in Guangdong and to assess the strengths and weaknesses of their teaching practices. It sought to test whether this tool could be used to measure teaching practices in the context of China and how to introduce classroom observations into a quality assurance and monitoring and evaluation (QAME) system, as well as exploring how to establish the preconditions for introducing results-based financing (RBF) into China.